Early development and coloniality in Oligophylloides from the Devonian of Morocco- Are Heterocorallia Palaeozoic octocorals? - Berkowski, Blazej; Zapalski, Mikolaj K.; Jarochowska, Emilia; Alderslade, Phil (PLoS ONE, 2021)
Heterocorals represent an enigmatic group of Palaeozoic corals, known from relatively short time intervals in the Devonian and Carboniferous periods. The major differences between Heterocorallia and other Palaeozoic corals are the lack of an external theca (epitheca), lack of calices and the presence of dichotomously dividing septa-like structures. Heterocoral skeleton was presumably externally covered by the soft tissue and each branch of their skeleton has, until now, been regarded as a corallite-a skeleton of a single polyp. We investigated upper Famennian Oligophylloides from Morocco, focussing on branching processes, wall structure, previously poorly known initial growth stages and the growing tip, described here for the first time. We demonstrate that Oligophylloides shows a unique colony development not known in any group of anthozoans possessing a septate-like architecture and suggest that the previously postulated homology between true septa in hexa- and rugose corals on one hand, and Oligophylloides on the other, must be rejected. Based on the skeleton structure and branching patterns, we postulate, contrary to former ideas, that the stem and branches of heterocorals represent the skeleton of a multi-polyp colonial coral, similar to many extant octocorals. We found numerous potential homologies with octocoral skeletons (notably the Keratoisidinae within the Isididae) and, as a result, we propose the inclusion of the order Heterocorallia within the subclass Octocorallia. This suggestion requires, however, further research on the other taxa of heterocorals. We also propose some changes to the morphological terminology for the Heterocorallia.
CRIS-Team Scopus Importer:2021-10-22